Political Stability and Human Development in The Organization of Islamic Cooperation (OIC) Countries - Wibowo, Muhammad Ghafur (Jurnal Ilmiah Ekonomi Islam, 2023)
In many Muslim countries, there are dynamics in political stability and security issue. This study examines the relationship between political stability and human development in the Organization of Islamic Cooperation (OIC) member countries. The political stability variable comes from the governance index published by the World Governance Indicator (WGI), which measures political stability, absence of violence, and terrorism. Secondary data on the Human Development Index (HDI) variable comes from the World Bank. This study analyzes 50 OIC member countries for 2003-2021 by employing the Granger causality method for panel data. The results show a bidirectional causality between the political stability index and the human development index in all OIC member countries. However, in countries with a very high HDI, the relationship between the two variables is unidirectional. In contrast, in the group of countries with a high and low HDI, the two variables have no connection.